FIQIH KONTEMPORER: APLIKASI DAN RELEVANSINYA DALAM KONTEKS MASYARAKAT MODERN - Robi'ah Robi'ah; Mela Ernia Sari; Nadila Juanda (CV. Denasya Smart Publisher, 2025)
Contemporary fiqh is a branch of jurisprudence designed to answer the challenges and problems of Islamic law in the context of the modern era. By paying attention to developments in science, technology and existing social dynamics, contemporary jurisprudence seeks to provide legal solutions that are relevant and applicable in various sectors of life. This research aims to export contemporary applications of fiqh and its relevance in modern society. With a responsive and flexible approach, contemporary fiqh is able to adapt to changing times without ignoring the basic principles of Islam. The findings of this research show that contemporary fiqh not only offers solutions to social problems such as contemporary issues in Islamic education but contemporary fiqh answers challenges and opportunities in its development.